Accelerated Generation of Selfed Pure Line Plants for Gene Identification and Crop Breeding - Yan, Guijun; Liu, Hui; Wang, Haibo; Lu, Zhanyuan; Wang, Yanxia; Mullan, Daniel; Hamblin, John; Liu, Chunji (Frontiers in Plant Science, 2017)
Production of pure lines is an important step in biological studies and breeding of many crop plants. The major types of pure lines for biological studies and breeding include doubled haploid (DH) lines, recombinant inbred lines (RILs) and near isogenic lines (NILs). DH lines can be produced through microspore and megaspore culture followed by chromosome doubling while RILs and NILs can be produced through introgressions or repeated selfing of hybrids. DH approach was developed as a quicker method than conventional method to produce pure lines. However, its drawbacks of genotype-dependency and only a single chance of recombination limited its wider application. A recently developed fast generation cycling system (FGCS) achieved similar times to those of DH for the production of selfed pure lines but is more versatile as it is much less genotype-dependent than DH technology and does not restrict recombination to a single event. The advantages and disadvantages of the technologies and their produced pure line populations for different purposes of biological research and breeding are discussed. The development of a concept of complete in vitro meiosis and mitosis system is also proposed. This could integrate with the recently developed technologies of single cell genomic sequencing and genome wide selection, leading to a complete laboratory based pre-breeding scheme.